Kearifan Lokal Pada Sistem Kekerabatan (Dalihan Na Tolu dan Rakut Si Telu) Pada Masyarakat Batak Toba - Gadis Prasiska Sembiring (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The kinship system is a very important part of the social structure.The kinship system of a society can be used to describe the social structure of the society in question. Local wisdom in the Darihan Natolu and Rakut Sitelu kinship systems shows that the Karo people have developed a kinship system that is unique and different from other communities in Indonesia.This kinship system also influences the way the Karo people interact and understand social and cultural life.